EFFECT OF AGGREGATE QUALITY ON THE PROPERTIES OF CONCRETE - Al-Dulaijan, S. U. (2020)
This paper presents results of a study conducted to evaluate the effect of aggregate quality, particularly when they do not comply with the standard requirements, on the properties of concrete. Crushed limestone aggregates from six quarries, five of which did not satisfy one or more of the ASTM C 33 requirements, were utilized to prepare concrete specimens. The concrete specimens were tested to evaluate the mechanical properties, and sulfate- and corrosion-resistance. The results indicate that some of the drawbacks in terms of the C 33 criteria did not affect the physical properties and durability performance of concrete. The excessive magnesium soundness loss noted in some of the aggregates also did not influence the sulfate resistance of concrete.